2015
DOI: 10.1007/s10549-015-3629-3
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of BRCA1 and BRCA2 alleles in Latin America and the Caribbean: a clinical perspective

Abstract: Hereditary cancer predisposition gene testing allows the identification of individuals at high risk of cancer that may benefit from increased surveillance, chemoprevention, and prophylactic surgery. In order to implement clinical genetic strategies adapted to each population’s needs and intrinsic genetic characteristic, this review aims to present the current status of knowledge about the spectrum of BRCA pathogenic variants in Latin American populations. We have conducted a comprehensive review of 33 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 97 publications
9
99
0
1
Order By: Relevance
“…Only 10.4% of BRCA mutations (n = 17) were shared between the US Hispanics and Latin America, and BRCA2 c.5946delT variant is one of the most frequently observed in Latin America (except for Mexico) but has still not been described in the US Hispanics. BRCA1 c.5123C>A is among the ten most frequent pathogenic variants in Latin America and has been reported in four countries of the region, despite it is not one of the most worldwide frequent BRCA1 variant [52]. They found that c.68 69delAG, c.5266dupC and c.4327C>T variants are frequent in Latin America and are among the 20 most frequent BRCA1 variants reported by the Breast Cancer Information Core (BIC) database.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 10.4% of BRCA mutations (n = 17) were shared between the US Hispanics and Latin America, and BRCA2 c.5946delT variant is one of the most frequently observed in Latin America (except for Mexico) but has still not been described in the US Hispanics. BRCA1 c.5123C>A is among the ten most frequent pathogenic variants in Latin America and has been reported in four countries of the region, despite it is not one of the most worldwide frequent BRCA1 variant [52]. They found that c.68 69delAG, c.5266dupC and c.4327C>T variants are frequent in Latin America and are among the 20 most frequent BRCA1 variants reported by the Breast Cancer Information Core (BIC) database.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%
“…Dutil et al performed a review of publications between 1994 and 2015 about BRCA evaluation in Hispanics and describe that only 8.02% (n = 13) of the reported pathogenic variants were present in two or more Latin American countries [52]. Only 10.4% of BRCA mutations (n = 17) were shared between the US Hispanics and Latin America, and BRCA2 c.5946delT variant is one of the most frequently observed in Latin America (except for Mexico) but has still not been described in the US Hispanics.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%
“…A review examined the spectrum of BRCA1 and BRCA2 mutations in Latin America and the Caribbean using studies published between the years 1994 and 2015. 22 Six of the 33 studies were conducted among Latina living in the United States, with the vast majority of participants drawn from clinic-based samples of patients of Mexican origin with breast cancer residing in California, Arizona, and Texas. 22 Prevalence estimates of carrying a BRCA mutation for this US Latina group ranged from 0.7% to 42% and varied based on whether cases were selected or unselected for family history or clinical characteristics (eg, affected vs unaffected, age at diagnosis), cancer site (eg, breast, ovarian), and type of testing (eg, inclusion of large rearrangement testing).…”
Section: High and Moderate Penetrance Genesmentioning
confidence: 99%
“…22 Six of the 33 studies were conducted among Latina living in the United States, with the vast majority of participants drawn from clinic-based samples of patients of Mexican origin with breast cancer residing in California, Arizona, and Texas. 22 Prevalence estimates of carrying a BRCA mutation for this US Latina group ranged from 0.7% to 42% and varied based on whether cases were selected or unselected for family history or clinical characteristics (eg, affected vs unaffected, age at diagnosis), cancer site (eg, breast, ovarian), and type of testing (eg, inclusion of large rearrangement testing). 22 In the cohorts of unselected patients with breast cancer, the BRCA mutation prevalence was 1.2% to 4.9%, which was consistent with expected rates.…”
Section: High and Moderate Penetrance Genesmentioning
confidence: 99%
“…This is also important to be taken into account in women from Latin American countries where the prevalence of BRCA mutations (ranging from 1.2 to 4.9%) is very similar to that of the non-Hispanic population in the USA 71 . Specific issues should be considered in the field of fertility preservation in cancer patients for BRCA carriers.…”
Section: Future Perspectivesmentioning
confidence: 99%